Perencanaan Dan Perancangan Wellness Center Dengan Pendekatan Healing Environment Di Desa Angseri, Baturiti, Tabanan, Bali - Michael Cartens Bahy Bahy; Ni Wayan Meidayanti Mustika; I Ketut Sugihantara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
The island of Bali is one of the main tourist spa destinations in the central part of Indonesia and is also one of the best tourist destinations in the world. The response to the development of tourism shown by the government with the creation of the Fitness Travel Book "Journey for Healthy Life". One of the districts that has begun to develop quite well from tourism activities is Tabanan Regency, but based on observations and interviews on one of the users of the Wellness Center facility in Tabanan Regency the existence of Wellness Center does not yet exist and some Wellness Center facilities such as retreats, yoga and meditation have not been established. Based on the results of the methodology, the results obtained in the form of Planning and Design with a Healing Environment Approach that is in accordance with the functions and characteristics of the Wellness Center. This Healing Environment approach is able to accelerate the recovery time of patient health or accelerate the patient's adaptation process from chronic and acute conditions by involving the psychological effects of patients in it. Healing Environment is a therapeutic environment design that combines natural, sensory and psychological elements. Then a concept of Planning and Design with a Healing Environment Approach in Angseri Village, Baturiti, Tabanan, Bali.